Water-metal mixed metamaterial wave absorber and application thereof
By designing a water-metal hybrid metamaterial absorber, using multi-layer structure and specific structural parameters, the three-frequency point absorption in the low-frequency band is achieved, solving the problem of poor effect of the existing medium and low-frequency band absorbers, and realizing the Miniaturized design and frequency regulation are suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411258178.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-09
AI Technical Summary
In the low-frequency electromagnetic band, existing metamaterial absorbers are difficult to achieve good wave absorption performance, and there are challenges in size control and material parameter setting, resulting in poor application effect in the low-frequency band.
Design a water-metal hybrid metamaterial absorber, adopting a multi-layer structure, including a metal base plate, an air layer, a FR4 dielectric plate, a metal pattern layer and a water layer, and wraps the water layer through a plexiglass layer, with the metal pattern layer being Made of copper material, it has specific structural parameters to achieve three-frequency point absorption in the low frequency band, and regulates the operating frequency and efficiency by adjusting the thickness of the air layer.
It realizes nearly perfect absorption of three-frequency points at low frequency band 0-1GHz, has a simple and miniaturized design and good wave absorption effect, and can also control the operating frequency range and efficiency of the absorber by changing the thickness of the air layer, which is suitable for a variety of applications. Scene.
Smart Images

Figure CN119181983A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electromagnetic metamaterials and relates to a water-metal hybrid metamaterial absorber and applications thereof. Background Art
[0002] In the vast field of electromagnetic spectrum, microwave frequency band is an indispensable part, and its frequency range covers 300MHz-300GHz. Usually researchers focus on the low-frequency part of microwave frequency band, that is, the frequency range is in the range of 300MHz-3GHz. Low-frequency electromagnetic waves have the characteristics of large wavelength, strong penetration ability, wide coverage, and low propagation loss. These excellent characteristics make them show extremely important application value in many fields such as wireless communication, radar detection, and electromagnetic stealth.
[0003] With the popularization of low-frequency electromagnetic wave applications, while it provides many conveniences, it is also accompanied by potential hazards that cannot be ignored. Long-term exposure to electromagnetic environments will pose a threat to the environment and human health, and will also cause electromagnetic interference, thereby disrupting the normal operation of equipment. Therefore, low-frequency electromagnetic shielding technology came into being and became the key to solving such problems. The application range of low-frequency electromagnetic shielding technology is very wide. In the field of communications, it can be used to protect communication equipment from external electromagnetic interference and ensure the stability and reliability of communications. In the military field, low-frequency electromagnetic shielding technology is often used in electromagnetic stealth technology, which can reduce the risk of being detected by enemy radar. At the same time, it can also be used to design stealth communication equipment to ensure the safety of military communications. In the medical field, low-frequency electromagnetic shielding technology can be used to protect medical equipment from electromagnetic interference, ensuring the normal operation of medical equipment and the safety of patients.
[0004] Metamaterials are man-made composite materials with extraordinary physical properties. Based on their unique electromagnetic properties, metamaterials have been widely studied in the fields of negative refractive index, polarization conversion, stealth technology, and electromagnetic wave absorption. Among them, the perfect absorption of electromagnetic waves has become one of the research hotspots in the field of metamaterials. Most existing electromagnetic metamaterial absorbers are generally multilayer structures composed of metal patterns-dielectric plates-metal backplanes. Through the magnetic loss, dielectric loss or ohmic loss of the material, the electromagnetic wave energy is converted into other forms of energy, thereby achieving the effect of absorbing electromagnetic waves. With the in-depth study of electromagnetic metamaterial absorbers, many metamaterial absorbers with application value have emerged in the microwave band and even the terahertz band. However, in the low frequency band, the excessively large wavelength brings great challenges to the electromagnetic parameter setting and size control of the absorbing material, resulting in the design of the metamaterial absorber. It is difficult to have good absorbing performance and it is also difficult to achieve. In recent years, the research on water-based metamaterials in the field of electromagnetic absorbers has attracted widespread attention from scholars. Water has the advantages of being clean, easy to regenerate, low price, and stable chemical properties. At microwave frequencies, water has a high dielectric constant and exhibits strong frequency dispersion characteristics, which makes it have a high dielectric loss for electromagnetic waves in a wide band, which is conducive to broadband absorption in the microwave band. However, in the low-frequency band, there are relatively few studies on water-based metamaterial absorbers, but their potential application value cannot be ignored. Summary of the invention
[0005] The present invention provides a water-metal hybrid metamaterial absorber and application thereof, wherein the absorber can realize absorption of three frequency points at low frequencies of 0-1 GHz, and also has a real-time regulation function of operating frequency range and efficiency.
[0006] In order to achieve the above objectives, the present invention adopts the following technical solution: a water-metal hybrid metamaterial absorber, which includes a plurality of periodically arranged structural units, wherein the structural units are in the shape of a cuboid, and from bottom to top are respectively a metal bottom plate layer, an air layer, a dielectric plate layer, a metal pattern layer and a water layer, wherein an organic glass layer is provided above the water layer, and an organic glass layer is provided between the air layer and the dielectric plate layer.
[0007] Furthermore, the length of the structural unit is 59-60 mm, the width is 29-30 mm, and the thickness is 12.40-12.50 mm. Furthermore, the metal bottom plate layer is made of copper material with a thickness of 0.025 mm to 0.035 mm.
[0008] Furthermore, the thickness of the air layer is 1-1.2 mm.
[0009] Furthermore, the dielectric board layer is FR4, the dielectric constant is 4.2~4.3, and the thickness is 1~1.2mm.
[0010] Furthermore, the water layer thickness is 8.0 mm to 8.6 mm.
[0011] Furthermore, the metal pattern layer is located on the upper surface of the dielectric board layer and is an axially symmetrical or centrally symmetrical figure; the metal pattern layer includes two semicircles, a slit circular ring between the two semicircles, and a cross structure composed of two mutually perpendicular rectangles of the same length and width in the slit circular ring; the center of the semicircle is located at the center of the wide side of the dielectric board layer, the center of the slit circular ring coincides with the center of the cross, and the slit circular ring is provided with two slits, which are perpendicular to the long side direction of the dielectric board layer.
[0012] Furthermore, the metal pattern layer is made of copper material, with a thickness of 0.025 mm to 0.035 mm and a width of 2.8 to 3 mm.
[0013] Furthermore, the radius of the semicircle is 13.5~14mm; the inner diameter and outer diameter of the slit ring are 11.5~12mm and 14.5~15mm respectively, and the slit width is 2.8~3mm; the length and width of the rectangle forming the cross structure are 13.5~14mm and 2.8~3mm respectively.
[0014] The present invention also relates to the application of the water-metal hybrid metamaterial absorber in the fields of electromagnetic absorption and electromagnetic shielding.
[0015] The present invention has the following beneficial effects: 1. The absorber based on water-metal hybrid metamaterial of the present invention achieves nearly perfect absorption of three frequency points (0.45GHz, 0.65GHz, 0.95GHz) in the low frequency band 0-1GHz. The structural size of the present invention is 60×30mm. Under the premise of the same absorber effect, the size of the present invention is smaller and the structure is simpler than that of the absorber of the same type. Therefore, the absorber of the present invention takes into account both simple miniaturization design and good absorbing effect in the low frequency band.
[0016] 2. The present invention realizes regular regulation of the working frequency range and efficiency of the absorber by changing the thickness of the air layer, has better practical application value, and can be applied to more application scenarios.
[0017] 3. The materials used in the present invention are all conventional materials and are easy to implement. In addition, the structure of the present invention is loaded with water materials, which are easy to obtain and have a lower cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 (a), (b) and (c) are respectively a unit structure diagram, a side view of the unit structure and a top view of the metal pattern layer of the water-metal hybrid metamaterial absorber of Example 1.
[0019] Figure 21 is an overall structural diagram of the water-metal hybrid metamaterial absorber of Example 1.
[0020] Figure 3 This is a graph showing the absorption rate of the water-metal hybrid metamaterial absorber of Example 2 with different structures removed.
[0021] Figure 4 This is a graph showing the absorption rate of the water-metal hybrid metamaterial absorber of Example 3 at different polarization angles.
[0022] Figure 5 This is a graph showing the absorption rate of the water-metal hybrid metamaterial absorber of Example 3 at different incident angles.
[0023] Figure 6 This is a curve diagram of the change in the absorption rate of the water-metal hybrid metamaterial absorber of Example 4 with the water layer thickness d2.
[0024] Figure 7 (a) and (b) are respectively a schematic diagram of the rotation of the slotted ring in the water-metal hybrid metamaterial absorber of Example 5 and a curve diagram of the change of the absorption rate with the rotation angle Φ.
[0025] Figure 8 This is a curve diagram of the absorption rate of the water-metal hybrid metamaterial absorber of Example 6 as a function of the air layer thickness d4.
[0026] Fig. 9 This is a graph showing the absorption rate of the water-metal hybrid metamaterial absorber in Example 7 with different structures removed from the metal pattern layer. DETAILED DESCRIPTION
[0027] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0028] Example 1 The unit structure of the water-metal hybrid metamaterial absorber model provided in this embodiment is as follows: Figure 1 As shown in (a), the internal structure is a rectangular parallelepiped consisting of a water layer, a metal pattern layer, a FR4 dielectric layer, an air layer, and a metal bottom plate at the back. Since water has fluid properties, the water layer and the dielectric layer are wrapped with organic glass to prevent water leakage. The side view of the unit structure is shown in Figure 1 As shown in (b), the thickness of the organic glass layer is d1 = 1 mm. The thickness of the water layer composed of water (Debye model) is d2 = 8.4 mm, and the relative dielectric constant of the dielectric layer FR4 below is , the tangent of the loss angle is , the thickness is d3 = 1mm, the thickness of the air layer below the dielectric plate is d4 = 1mm, the bottom metal base plate and the metal pattern layer above the dielectric plate are both made of The metal pattern layer is made of copper, and the corresponding thickness is 0.035mm. The top view of the structure of the metal pattern layer is as follows Figure 1 As shown in (c), the left and right parts are two symmetrical semicircles, and the middle part is composed of a slit ring and a cross structure, where the width of the ring slit is the same as the width of the cross strip. Other structural parameters: w=12mm, k=3mm, W=14mm, R=15mm, r=12mm, the overall length and width of the model are p=60mm, q=30mm. Multiple unit structures are arranged closely and periodically, and the overall structure is shown as follows Figure 2 shown.
[0029] Example 2 The metamaterial absorber of the present invention is composed of a water-metal mixed material. Its multi-frequency point and high absorption rate absorption performance is related to the characteristics of the metal pattern layer and the water layer. In order to better analyze the influence of different structures in the absorber on the absorption characteristics, the metal layer and the water layer are removed respectively and compared with the designed structure. The simulation calculation results are shown in the figure. Figure 3 As shown, structure 1 retains the metal layer and the water layer, structure 2 retains the water layer and removes the metal layer, and structure 3 retains the metal layer and removes the water layer. Figure 2 It can be seen that when the water layer is removed, the absorber has basically no absorption effect on electromagnetic waves. At the same time, due to the presence of the metal bottom plate, the whole is in a state of total reflection, which shows that the presence of the water layer is crucial to the absorption effect. When the metal pattern layer is removed, there is only one absorption frequency point of 0.71GHz in the low frequency band, and the absorption rate is far from 90%, which shows that there is a close connection between the metal structure and the wave absorption characteristics. When the water layer and the metal structure are combined to form Figure 1 When the structure is shown, the corresponding absorption curve is as follows Figure 3As shown, there are absorption peaks at 0.45GHz, 0.65GHz, and 0.95GHz, and the absorption rates reach 97.4%, 98.1%, and 98.3%, achieving near-perfect absorption at three frequency points at low frequencies. Since direct contact between water and metal copper will cause corrosion of metal copper, it is considered to wrap the metal pattern layer with a certain material to prevent direct contact between metal and water. Based on the above considerations, the selected material needs to meet the requirements of corrosion resistance, transparency to low-frequency electromagnetic waves, and compatibility with copper materials. PTFE is used here to cover the metal pattern layer to prevent metal corrosion. PTFE (polytetrafluoroethylene film) has a low dielectric constant and dielectric loss, and has good transmittance for low-frequency electromagnetic waves. Compared with high-frequency electromagnetic waves, the reflection and absorption of low-frequency electromagnetic waves in PTFE are weaker. At the same time, PTFE also has extremely strong corrosion resistance, can withstand the erosion of a variety of corrosive media such as strong acids, strong alkalis, organic solvents, and performs well in water corrosion environments.
[0030] Example 3 In order to study the functional mechanism of the water-metal hybrid metamaterial absorber of the present invention, the absorption frequency and absorption rate under different incident angles and polarization angles were studied. When electromagnetic waves are incident at different polarization angles, the corresponding absorption spectra are as follows: Figure 4 As shown in Figure 1, at the first resonant frequency, when the polarization angle is less than 30°, the resonant frequency and absorption rate do not change substantially. When the resonant frequency does not change, the absorption rate decreases by about 10%. The second resonant frequency gradually moves toward the low frequency direction with the increase of the polarization angle. The decrease in absorption rate with the change of polarization angle can be ignored. , at this time, the worst absorption effect is 97.0%, and the curve with absorption rate greater than 90% becomes flat, and the absorption bandwidth becomes wider. The third resonant frequency changes slightly with the increase of polarization angle. When the polarization angle is less than 45°, the absorption rate of the resonant frequency remains unchanged. When the polarization angle is 45°, the absorption rate drops sharply, close to 83%, and a new absorption frequency appears at 1.12GHz. It can be seen from the above that when the polarization angle is less than 30°, the wave absorption characteristics of the absorber change slightly with the polarization angle. When the polarization angle is greater than 30°, the wave absorption effect of the absorber changes significantly, indicating that the absorber has polarization-sensitive characteristics. Figure 5The absorption curve of the designed metamaterial at different incident angles. It can be seen from the figure that when the incident angle changes between 0-60°, the frequencies of the three resonant frequencies remain basically unchanged, but the absorption rate shows a downward trend as a whole. When the incident angle is 60°, the absorption effect of the model is the worst. The resonant frequencies are distributed at 0.45GHz, 0.65GHz, and 0.94GHz, and the corresponding absorption rates are 96.0%, 95.0%, and 95.4% respectively. Compared with the vertical incidence of electromagnetic waves, the absorption rates of each resonant point have decreased, and the second frequency point has the largest decrease, which has decreased by 3.1%, but the overall decrease is small and still has a good absorption effect after the decrease. From the above, it can be seen that the absorber still has a good absorption effect on the corresponding frequency point of obliquely incident electromagnetic waves, and the change of the incident angle can be ignored. The influence of the wave absorption characteristics of the absorber can be ignored, indicating that the absorber has the characteristics of wide-angle incidence.
[0031] Example 4 The simulation test was carried out by CST simulation software. In order to obtain the optimal structural parameters, the structural parameters were studied by using the parameter scanning analysis method based on the control variable method. First, the effect of the water layer thickness on the absorption frequency and absorption rate was studied. Figure 6 As shown in the figure, when d2=7.4mm, the absorption rates of the three resonance points all reach more than 99%, which has an extremely high absorption rate, but the frequency of the third frequency point exceeds the ideal operating frequency range (1GHz). When d2=8.4mm, the three resonance frequencies are all within 1GHz, and the absorption rates all reach more than 97%. The absorption frequency points are in the low frequency band while ensuring good absorption rates. When d2=10.4mm, compared with d2=8.4mm, the three resonance frequencies are basically unchanged, and the maximum decrease in absorption rate at the resonance frequency points is only 1%. Considering that miniaturized metamaterial absorbers in low frequency bands can better adapt to practical applications, a thinner water layer thickness is selected when the absorption characteristics are basically the same. At the same time, in order to achieve an operating frequency range below 1GHz, 8.4mm is selected as the model size for the water layer thickness.
[0032] Example 5 Study on the effect of the rotation angle of the slotted ring on the absorption frequency and absorption rate of the metamaterial absorber Keep the structure and parameters of other layers unchanged, and only adjust the angle of the slit ring. The specific angles are 30°, 60°, and 90°. The metal layer pattern after rotation is as follows Figure 7 (a) shows an asymmetric metal structure, and then the absorption rate at different rotation angles is simulated. The simulation results are shown in Figure 7 (b). Figure 7(b) shows that, at the first absorption frequency point, as the rotation angle increases, the resonant frequency shifts greatly. Compared with the rotation angle of 0°, the absorption rate after rotation decreases significantly, and the absorption effect of more than 90% cannot be guaranteed. At the second absorption frequency point, when the rotation angle is less than 90°, the resonant frequency moves toward the low-frequency direction, and the absorption rate shows a slight upward trend, reaching 99% when rotated 60°. When the rotation angle is equal to 90°, the resonant frequency moves toward the high-frequency direction, and the absorption rate remains basically unchanged. At the third absorption frequency point, when the rotation angle is 30°, the resonant frequency moves toward the low-frequency direction, and the absorption rate shows an upward trend. When the rotation angle is 60°, the resonant frequency moves toward the high-frequency direction, and the absorption rate shows an upward trend. When the rotation angle is 90°, the changes in the resonant frequency and the absorption rate are very weak compared to 0°. From the above, it can be seen that when the slit ring is rotated so that the structure cannot guarantee the symmetric characteristics, it has a significant impact on the frequency band where the resonant frequency point is located, especially the absorption rate of the first frequency point.
[0033] Example 6 The same method is used to analyze the influence of the air layer thickness of the metamaterial absorber on the simulation effect. The simulation calculation results of the model absorption rate under different air layer thicknesses are shown in the following figure. Figure 8 As shown. In the air layer thickness In the process of increasing from 0 to 4 mm: the resonance frequency of the first absorption frequency point moves toward the low frequency direction as the thickness of the air layer increases, and the absorption rate shows a trend of first decreasing and then increasing. The absorption rate reaches its maximum value (100%) when the air layer thickness increases, and can still reach an absorption effect of more than 80% at other air layer thicknesses. The resonant frequency of the second absorption frequency point moves toward the low frequency direction as the air layer thickness increases, and the absorption rate shows an overall upward trend. The absorption rate reaches more than 99%. The resonance frequency of the third absorption frequency point moves toward the low frequency direction with the increase of the air layer thickness, and its absorption rate shows a slight downward trend. It reaches the lowest when the air layer is 100%, but it can still guarantee an absorption effect of about 98%. From the above analysis, it can be seen that with the increase of the thickness of the air layer, the resonance frequencies of the three absorption frequencies all move toward the low frequency direction, the absorption rate of the first frequency point shows a trend of first rising and then falling, the absorption rate of the second frequency point shows an upward trend, and the absorption rate of the third frequency point shows a slight downward trend. The results show that the operating frequency can be adjusted by changing the thickness of the air layer, and the absorption efficiency does not change much. Therefore, the designed metamaterial absorber has adjustable characteristics.
[0034] Example 7 Through the analysis of Example 2, it can be seen that the wave absorption effect of the three-frequency points of the metamaterial is closely related to the existence of the metal pattern layer. In order to explore the influence of each structure of the metal layer on the wave absorption effect of the metamaterial, two groups of structures, a ring with a slit removed and a semicircle with a symmetric shape, are set up for comparison with the original structure. The absorption rate curve obtained by simulation is as follows: Fig. 9 As shown. When the slit ring is removed, the first absorption frequency disappears, and the second and third absorption frequencies move toward the low frequency direction as a whole, and the absorption rate of the second absorption frequency is significantly reduced. This shows that the existence of the slit ring is very critical to the first and second absorption frequencies. When the symmetrical semicircle is removed, the third absorption frequency disappears, and the absorption rate of the second absorption frequency is significantly reduced, and the absorption frequency moves toward the high frequency direction, which shows that the existence of the symmetrical semicircle is very important to the second and third absorption frequencies. The above simulation experimental results show that the existence of the slit ring directly determines the existence of the first absorption frequency, and the symmetrical semicircle determines the existence of the third absorption frequency. At the same time, according to the analysis of Example 2, when the metal layer is removed and the water layer is retained, there is only one absorption frequency (i.e., the second frequency) and the absorption rate of the absorption frequency is low, and the existence of the slit ring and the symmetrical semicircle has a great influence on the absorption rate of the second absorption frequency. Therefore, the slit ring and the symmetrical semicircle structure in the metal pattern layer have a very important influence on the wave absorbing effect of the metamaterial.
[0035] In summary, the present invention proposes a water-metal hybrid metamaterial absorber. The device can achieve near-perfect absorption at three frequency points at low frequencies of 0-1 GHz, has polarization sensitivity, wide-angle incident wave absorption characteristics, and can dynamically adjust the operating frequency range and absorption efficiency by changing the thickness of the air layer.
[0036] The above embodiments describe the preferred implementation of the present invention, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A water-metal hybrid metamaterial absorber, characterized in that: The absorber comprises a plurality of periodically arranged structural units, each of which is in the shape of a cuboid and comprises, from top to bottom, a metal bottom plate layer, an air layer, a dielectric plate layer, a metal pattern layer and a water layer, wherein an organic glass layer is arranged above the water layer, and an organic glass layer is arranged between the air layer and the dielectric plate layer.
2. The absorber according to claim 1, characterized in that: The length of the structural unit is 59~60mm, the width is 29~30mm, and the thickness is 12.40~12.50mm.
3. The absorber according to claim 2, characterized in that: The metal bottom plate layer is made of copper material with a thickness of 0.025mm~0.035mm.
4. The absorber according to claim 1, characterized in that: The thickness of the air layer is 1~1.2mm.
5. The absorber according to claim 1, characterized in that: The dielectric board layer is FR4 with a dielectric constant of 4.2~4.3 and a thickness of 1~1.2mm.
6. The absorber according to claim 1, characterized in that: The thickness of the water layer is 8.0mm~8.6mm.
7. The absorber according to any one of claims 1 to 6, characterized in that: The metal pattern layer is located on the upper surface of the dielectric plate layer and is an axisymmetric or center-symmetrical figure; the metal pattern layer includes two semicircles, a slotted circular ring between the two semicircles, and a cross structure composed of two rectangles of the same length and width that are perpendicular to each other in the slotted circular ring; the center of the semicircle is located at the center of the wide side of the dielectric plate layer, the center of the slotted circular ring coincides with the center of the cross, and the slotted circular ring is provided with two slots that are perpendicular to the long side direction of the dielectric plate layer.
8. The absorber according to claim 7, characterized in that: The metal pattern layer is made of copper material, with a thickness of 0.025 mm to 0.035 mm and a width of 2.8 to 3 mm.
9. The absorber according to claim 7, characterized in that: The radius of the semicircle is 13.5~14mm; the inner and outer diameters of the slit ring are 11.5~12mm and 14.5~15mm respectively, and the slit width is 2.8~3mm; the length and width of the rectangle that makes up the cross structure are 13.5~14mm and 2.8~3mm respectively.
10. Application of the water-metal hybrid metamaterial absorber according to any one of claims 1 to 9 in the field of electromagnetic absorption and electromagnetic shielding.
Citation Information
Patent Citations
Water-based interlayer metasurface adjustable coherent wave absorber
CN113346249A
Water-based low-frequency metamaterial wave absorber
CN117638518A
Water-based transparent reconfigurable metamaterial wave absorber and manufacturing method thereof
CN117791161A
KR20240088092A
